HUBUNGAN OBESITAS SENTRAL DENGAN PROFIL LIPID PADA ORANG DEWASA UMUR 25-65 TAHUN DI KOTA BOGOR (Baseline Studi Penyakit Tidak Menular di Kota Bogor, Jawa Barat) - Sudikno, Sudikno; Syarief, Hidayat; Dwiriani, Cesilia Meti; Riyadi, Hadi; Pradono, Julianti (PERSATUAN AHLI GIZI INDONESIA, 2016)
The global epidemic of obesity is rapidly becoming a major public health problem in many countries of the world. Rapidly changing diets and lifestyles are trigger to the global obesity epidemic. This study aimed to determine the prevalence of central obesity and the relationship between central obesity and lipid profile in adults aged 25-65 years. This study used baseline data